2017
DOI: 10.1002/ecs2.1787
|View full text |Cite
|
Sign up to set email alerts
|

A framework for modeling habitat quality in disturbance‐prone areas demonstrated with woodland caribou and wildfire

Abstract: Abstract. Natural resource management professionals require adaptable spatial tools for conserving and managing wildlife across landscapes. These tools should integrate multiple components of habitat quality and incorporate local disturbance regimes. We provide a spatial modeling framework that integrates three components of habitat (nutritional resources, connectivity, and predation risk) into indices of habitat quality under a simulated wildfire disturbance regime. Woodland caribou (Rangifer tarandus caribou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 57 publications
(109 reference statements)
0
19
0
Order By: Relevance
“…, Whitman et al. ). Furthermore, warmer winters may lead to more frequent thaw‐freeze or rain‐on‐snow icing events which can make vegetation under the snow inaccessible (Gunn , Albon et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Whitman et al. ). Furthermore, warmer winters may lead to more frequent thaw‐freeze or rain‐on‐snow icing events which can make vegetation under the snow inaccessible (Gunn , Albon et al.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, research has mainly focused on direct and indirect effects of climate on forage availability. For example, caribou winter forage comprises primarily slow-growing terrestrial lichens (Joly et al 2007(Joly et al , 2010 which are negatively impacted by the warming-induced increases in drought, wildfire regimes, and tree pathogens occurring throughout boreal regions (Joly et al 2009, de Groot et al 2013, Whitman et al 2017. Furthermore, warmer winters may lead to more frequent thaw-freeze or rain-onsnow icing events which can make vegetation under the snow inaccessible (Gunn 2003, causing mass mortalities in exceptional cases (Miller andBarry 2009, Forbes et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We included nutritional resources and risk of predation and disease (hereafter "habitat-quality modules") as the two components of habitat-quality most important for caribou. Reclassification weights for each season were derived from published studies that reported resource selection functions (Boyce et al 2002), supplemented by expertbased inference where necessary (Muhly et al 2015, Whitman et al 2017). Reclassification weights for each season were derived from published studies that reported resource selection functions (Boyce et al 2002), supplemented by expertbased inference where necessary (Muhly et al 2015, Whitman et al 2017).…”
Section: Model Overviewmentioning
confidence: 99%
“…Predation and disease.-We reclassified vegetation cover and patch age into two raster layers that accounted for the risk of predation by black bears, Whitman et al (2017). and the risk of predation and disease associated with white-tailed deer.…”
Section: Habitat-quality Modules and Inputsmentioning
confidence: 99%
See 1 more Smart Citation